Enhanced treatment of landfill leachate by biochar-based aerobic denitrifying bacteria functional microbial materials: Preparation and performance - Song, Jianyang; Li, Minghui; Wang, Chunyan; Fan, Yujie; Li, Yuan; Wang, Yongkun; Zhang, Wenxiao; Li, Haisong; Wang, Hongyu (Frontiers in Microbiology, 2023)
In this work, polyvinyl alcohol (PVA) and sodium alginate (SA) were used as entrapped carriers and Artemisia argyi stem biochar (ABC) was used as an absorption carrier to immobilize aerobic denitrifying bacteria screened from landfill leachate, thus a new carbon-based functional microbial material (PVA/SA/ABC@BS) was successfully prepared. The structure and characteristics of the new material were revealed by using a scanning electron microscope and Fourier transform infrared spectroscopy, and the performance of the material for treating landfill leachate under different working conditions was studied. The results showed that ABC had abundant pore structures and that the surface contained many oxygen-containing functional groups, carboxyl groups and amide groups etc. and it had good absorbing performance and strong acid and alkali buffering capacity, which was beneficial to the adhesion and proliferation of microorganisms. After adding ABC as a composite carrier, the damage rate of immobilized particles was decreased by 1.2%, and the acid stability, alkaline stability and mass transfer performance were increased by 9.00%, 7.00% and 56% respectively. When the dosage of PVA/SA/ABC@BS was 0.017g/mL, the removal rates of nitrate nitrogen (NO3--N) and ammonia nitrogen (NH4+-N) were the highest, which were 98.7% and 59.4% respectively. When the pH values were 11, 7, 1 and 9, the removal rates of chemical oxygen demand (COD), NO3--N, nitrite nitrogen (NO2--N) and NH4+-N reached the maximum values, which were 14.39%, 98.38%, 75.87% and 79.31%, respectively. After PVA/SA/ABC@BS was reused in 5 batches, the removal rates of NO3--N all reached 95.50%, which indicated that PVA, SA and ABC have excellent reusability for immobilization of microorganisms and degradation of nitrate nitrogen. This study can provide some guidance for the great application potential of immobilized gel spheres in the treatment of high concentration organic wastewater.